Analytical Study on Surface Settlement Troughs Induced by the Sequential Excavation of Adjacent and Parallel Tunnels in Layered Soils. (15th February 2022) - Dong, Cong; Lin, Jian; Cao, Guangyong; Cheng, Hua; Shi, Linlin; Zhang, Xiaohui
Abstract : In this paper, the settlement troughs induced by the excavation of adjacent and parallel tunnels in layered soils were studied. Firstly, a trough width parameter calculation method in layered soils was established based on the propagation model of the plastic zone and unloading disturbance zone. Secondly, the mechanism of the superposition disturbance between parallel tunnels is analyzed, and a method for calculating additional settlement trough is proposed. Finally, the applicability of the proposed model was demonstrated with two case studies of the parallel tunnels. The following conclusions were obtained: the difference of soil properties in layered soils had a significant influence on the width parameter of surface settlement trough; a Gaussian curve can describe the additional settlement caused by superimposed disturbance; and finally, the relationship between the ground loss induced by superposition disturbance and the ground loss induced by the preceding tunnel was approximately linear. The model presented in this paper is highly effective and convenient for use in practice and extends the calculation method of surface settlement trough based on the Gaussian curve.